A Warm Heart and a Clear Head - Keller, Matthew C.; Fredrickson, Barbara L.; Ybarra, Oscar; Côté, Stéphane; Johnson, Kareem; Mikels, Joe; Conway, Anne; Wager, Tor (Psychological Science, 2005)
Prior studies on the association between weather and psychological changes have produced mixed results. In part, this inconsistency may be because weather's psychological effects are moderated by two important factors: the season and time spent outside. In two correlational studies and an experiment manipulating participants' time outdoors (total N = 605), pleasant weather (higher temperature or barometric pressure) was related to higher mood, better memory, and “broadened” cognitive style during the spring as time spent outside increased. The same relationships between mood and weather were not observed during other times of year, and indeed hotter weather was associated with lower mood in the summer. These results are consistent with findings on seasonal affective disorder, and suggest that pleasant weather improves mood and broadens cognition in the spring because people have been deprived of such weather during the winter.